Socialization of Village Website Management in Pardinggaran Village: Sosialisasi Pengelolaan Website Desa di Desa Pardinggaran - Simbolon, Iustisia; Arie Satia Dharma; Herimanto, Herimanto; Tahan HJ Sihombing; Nenni Mona Aruan; Archico Darius Simpar Sembiring; Enrico Hezkiel Sirait; Wilona Diva Artha Simbolon; Emely Angelica Lestari (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Socialization of village website management in Pardinggaran Village is an activity that helps the government increase awareness among village officials that village websites are a medium for promoting village tourism potential and superior village products. This activity is based on the results of observations on the village website owned by Pardinggaran Village which is still not optimal in managing information related to the village. There is still very little information regarding Pardinggaran Village from the website. Lack of exposure to village activities can be one of the reasons for the lack of tourism development in the village. This is because Pardinggaran Village is a village located in Toba Regency which is a tourist destination area. So, based on these problems, this activity aims to provide innovative solutions in the form of socialization in managing village websites. Through this activity, it is hoped that it can help Pardinggaran Village in managing the village website optimally so that the village website can be used as a medium for information and promotion.